Marketing a Webinar: Lesson Learnt from a Real Experiment - Regina, Tamara; Maria, Joyceline; Yanson, Feliciya; Sepadyati, Nova; Agustin, Karina; Soewandi, Hanijanto (RSF Conference Series: Business, Management and Social Sciences, 2022)
Implementing an email campaign can powerfully and positively influence customers’ attitudes about the content of the email used as promotional media. However, email marketing efforts may not reach their full potential without evaluating their marketing strategy. This paper discusses the real-world experience of the email marketing strategy of the webinar that we managed by applying email marketing strategy evaluation combined with mathematical diffusion models to increase the number of registrations. After starting with a digital external campaign for our webinar event, we monitor and predict using Bass, von Bertalanffy, Gompertz, and Logistic. While the mathematical diffusion models show that our webinar reached a plateau very early, it could become an alarm for the management team to react and make another internal digital campaign to boost our webinar participants. Interestingly, we also encountered a procrastination phenomenon since this was a free webinar. Finally, using Zoom registration, MySQL database, and R, we analyzed how effective the digital email campaign was in getting registrants daily.